Dyscalculia and Typical Math Achievement Are Associated With Individual Differences in Number‐Specific Executive Function. Issue 2 (31st December 2018) - Wilkey, Eric D.; Pollack, Courtney; Price, Gavin R.
Abstract : Deficits in numerical magnitude perception characterize the mathematics learning disability developmental dyscalculia (DD), but recent studies suggest the relation stems from inhibitory control demands from incongruent visual cues in the nonsymbolic number comparison task. This study investigated the relation among magnitude perception during differing congruency conditions, executive function, and mathematics achievement measured longitudinally in children ( n = 448) from ages 4 to 13. This relation was investigated across achievement groups and as it related to mathematics across the full range of achievement. Only performance on incongruent trials related to achievement. Findings indicate that executive function in a numerical context, beyond magnitude perception or executive function in a non‐numerical context, relates to DD and mathematics across a wide range of achievement.